The Multimodality of the English Visual and Graphic Text - Бялик, Василь Дмитрович (Annals of the University of Craiova. Series Philology. Linguistics, 2023)
The article focuses on the issue of expressing multimodality in English-language comics. It has been established that multimodality is expressed at verbal, verbal-non-verbal, and non-verbal modes in English-language comics which are considered as visual and graphic texts. It was found out that all comic texts are represented by partial or complete multimodality. The complete multimodality implies a close connection with both lingual and visual components of a text space. The partial multimodality of the text presupposes a relative autonomy of a verbal constituent and its independence on imagery. The verbal component of expressing modality is represented at the phonetic, lexical, syntactic, textual levels of the language, as well as with deictic markers, and expressive means. The verbal-visual and visual proper multimodality means include the phonosemantic channel, paragraphemics, font typeface, colour.
Keywords: multimodality, visual and graphic text, English comics